Cardiovascular disease – coronary heart disease – qualitative research - Bell, Catherine (2010)
Abstract Background Cardiovascular disease is the leading cause of death worldwide (World Health Organisation, 2008). This study focuses coronary heart disease and the management of lifestyle changes in prevention and ongoing treatment. In doing this, cardiac rehabilitation most useful. Through this process, individuals may experience a variety of issues, which may influence their overall health status. Despite the importance of rehabilitation being acknowledged, there is need for all available literature to be synthesised, in order to understand the range of issues that the individuals encounter.